DETERMINANTS OF ENVIRONMENTALLY FRIENDLY HOME PURCHASE INTENTIONS AMONG THE YOUNGER GENERATION IN INDONESIA - Galih Ayu Sartika; Pawenang Supawi; Safiah Sidek; Massila Kamalrudin (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
In Indonesia, interest in environmentally friendly housing has increased over the past two decades. However, despite this high level of interest, growth has not been optimal. This study aims to analyze the factors influencing the intention to purchase an environmentally friendly home among the younger generation. The sample of this study was the younger generation, namely Generation Z and millennials. The sampling technique used purposive sampling and the data analysis method used PLS-SEM. The findings of this study indicate that the intention to purchase an environmentally friendly home among the younger generation is directly influenced by subjective norms, PBC, environmental concern, knowledge of environmentally friendly buildings, reasonable prices, and perceived value. Environmental concern and knowledge of environmentally friendly buildings are strong predictors in fostering positive attitudes among the younger generation towards the environment. Meanwhile, subjective norms and PBC are directly influenced by knowledge of environmentally friendly buildings. These findings underscore the importance of targeting the already high environmental concern among the younger generation. Enhancing PBC through price transparency and innovative financing options is crucial to bridging intentions and actions. Subjective norms can be leveraged through campaigns that highlight the